Molecular dynamics simulations and KcsA channel gating. - Shrivastava, I; Sansom, MS (2002)
The gating mechanism of a bacterial potassium channel, KcsA, has been investigated via multi-nanosecond molecular dynamic simulations of the channel molecules embedded in a fully solvated palmitoyloleoylphosphatidylcholine bilayer. Four events are seen in which a cation (K(+) or, in one case, Na(+)) initially present in the central cavity exits through the intracellular mouth (the presumed gate) of the channel. Whilst in the cavity a cation interacts with the sidechain T107 O gamma atom of one of the subunits prior to its exit from the channel. Secondary structure analysis as a function of time reveals a break in the helicity of one of the M2 helices. This break is expected to lend flexibility to the helices, enabling them to "open" (minimum pore radius >0.13 nm) and "close" (minimum pore radius <0.13 nm) the channel. Fluctuations in the pore radius at the intracellular gate region are of the order of 0.05 nm, with an average radius in the region of the gate of ca. 0.1 nm. However, around the time of exit of a cation, the pore widens to about 0.15 nm. The distances between the C alpha atoms of the inner helices M2 reveal a coupled increase and decrease between the opposite pair of helices at about the time of exit of the ion. This suggests a breathing motion of the M2 helices that may form the basis for a gating mechanism.